Provincializing Spotify: Radio, algorithms and conviviality. (1st April 2020) - Razlogova, Elena
Focusing on early experiments with algorithms and music streaming at WFMU, the longest-running US freeform radio station, and the Free Music Archive (FMA), a curated open music website, this article shows how commercial streaming services have been indebted to independent, open music infrastructures but have then erased and denied that history. The article 'provincializes' music streaming platforms such as Spotify by focusing not on their commercial aims but instead on the 'convivial', collaborative practices and spaces that their software engineers and users inhabited. I analyse an experimental national telephone broadcasting service at WFMU in 1989, an algorithmic WFMU radio stream 'The Flaming Robot of Love' during the Republican National Convention in 2004 and the 'Free Music Archive Radio App' that recommended tracks on the FMA website from 2011 to 2016. The app worked with an application programming interface (API) from Echo Nest. Echo Nests' algorithmic recommendation engine also powers most commercial streaming services today. When Spotify purchased Echo Nest in 2014 and took the start-up's open API offline in 2016, it engaged in 'primitive accumulation' of open-access knowledge and resources for commercial purposes. The FMA closed in 2019 and now only exists as a static site. As social institutions, however, WFMU and FMA 'recomposed' – adapted to a new medium and a new political context – collaborative engineering practices of the early broadcasting era. The article argues that moments of oppositional 'conviviality' in media culture such as the FMA should be analysed as elements of a continuous struggle.